2010
DOI: 10.3109/01612840903470609
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Abuse Among Female Nurses and Nursing Personnel: Prevalence and Risk Factors

Abstract: This study examines the prevalence and risk factors for intimate partner violence (IPV) and intimate partner abuse (IPA) against female nurses and nursing personnel (n = 1981). Data were collected through online surveys conducted at three hospitals and one geriatric care center in a Mid-Atlantic US metropolitan area. Lifetime physical or sexual IPV was reported by 25% of participants and 22.8% reported experiencing lifetime emotional abuse by an intimate partner. Logistic regression analyses identified indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 76 publications
8
57
3
3
Order By: Relevance
“…Thus, there seems to be a mismatch between the prevalence of violence and reported cases, in accordance with other studies conducted in Spain (21) . The prevalence obtained was similar to that of other studies conducted with health professionals in other countries: a study in Jordan found that 59% of the nurses had suffered psychological IPV (6) ; a study in the United States found that 25% of the nurses had suffered IPV (4) . The origin of the differences regarding prevalence of IPV in the different autonomous communities could be due to sociocultural differences or unequal development of gender equality and violence programs, among other causes (9,22) .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Thus, there seems to be a mismatch between the prevalence of violence and reported cases, in accordance with other studies conducted in Spain (21) . The prevalence obtained was similar to that of other studies conducted with health professionals in other countries: a study in Jordan found that 59% of the nurses had suffered psychological IPV (6) ; a study in the United States found that 25% of the nurses had suffered IPV (4) . The origin of the differences regarding prevalence of IPV in the different autonomous communities could be due to sociocultural differences or unequal development of gender equality and violence programs, among other causes (9,22) .…”
Section: Discussionsupporting
confidence: 74%
“…Only one study has been conducted in Spain focused exclusively on nursing staff, and it demonstrated the severity of the problem: 33% of the studied female nurses had experienced IPV (3,5) . The high prevalence found in that study corroborates the international literature, such as in the United States (4) and Jordan (6) , although there is a paucity of studies on the phenomenon among health professionals. Considering the above, it is important to determine the prevalence of IPV among health professionals, since health services usually assist IPV victims.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…14,15 Şiddete uğrayan kişinin bağlanma stillerinin değiştiği ve güvenli bağlanamadığı öne sürülmüştür. 16 Güvensiz bağlanma biçimleri psikopatolojilerle ilişkilendirilmekte ve bazı çalış-malarda aile içi şiddet mağduru olmakla güven-siz bağlanma arasında bir ilişki olduğundan bahsedilmektedir. [17][18][19] Uygulanan şiddetin kadın üzerindeki ruhsal etkilerinin, kişinin sahip olduğu başa çıkma mekanizmaları ve sosyal desteği ile ilişkili olduğu öne sürülmüştür.…”
Section: Introductionunclassified